2007
DOI: 10.1111/j.1745-6916.2007.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Proceeding From Observed Correlation to Causal Inference: The Use of Natural Experiments

Abstract: ABSTRACT-This article notes five reasons why a correlation between a risk (or protective) factor and some specified outcome might not reflect environmental causation. In keeping with numerous other writers, it is noted that a causal effect is usually composed of a constellation of components acting in concert. The study of causation, therefore, will necessarily be informative on only one or more subsets of such components. There is no such thing as a single basic necessary and sufficient cause. Attention is dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
363
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 324 publications
(369 citation statements)
references
References 151 publications
(155 reference statements)
5
363
0
1
Order By: Relevance
“…The difficulty with this latter strategy of course is that experiments of nature depend on serendipitous events that are outside the investigator's control. Rutter (Rutter, 2007;Rutter, Pickles, Murray, & Eaves, 2001) has recently shown, however, that several behavioral genetic research designs constitute experiments of nature and consequently provide unique opportunities for rigorous evaluation of causal hypotheses with observational data. We illustrate this aspect of contemporary behavioral genetic research with two examples of recent MCTFR research.…”
mentioning
confidence: 99%
“…The difficulty with this latter strategy of course is that experiments of nature depend on serendipitous events that are outside the investigator's control. Rutter (Rutter, 2007;Rutter, Pickles, Murray, & Eaves, 2001) has recently shown, however, that several behavioral genetic research designs constitute experiments of nature and consequently provide unique opportunities for rigorous evaluation of causal hypotheses with observational data. We illustrate this aspect of contemporary behavioral genetic research with two examples of recent MCTFR research.…”
mentioning
confidence: 99%
“…[4][5][6] Several approaches can be used to control for unmeasured confounding, and convergence of findings from different methods and cohorts provides the strongest support for causal claims. 7,8 In sibling control designs, siblings discordant for maternal smoking during pregnancy are compared with respect to ADHD. Some studies using this approach have suggested that the association between maternal smoking during pregnancy and offspring ADHD is due to unmeasured confounding, 9 -12 whereas a recent study suggested that the association may be causal.…”
mentioning
confidence: 99%
“…There is no point in studying the biological embedding of experiences whose risk effects are not environmentally mediated. It is all too often assumed that the remedy lies in the statistical control of confounders, but numerous studies using "natural experiment" designs have shown that reliance on such statistical control is a seriously flawed approach (4,5). Nevertheless, there is good evidence that physical and sexual abuse, as well as poverty, does have adverse causal effects.…”
Section: Causal Effects Of Early Experiencesmentioning
confidence: 99%
“…First, there are about a dozen different natural experiments that have been shown to be useful (2,5,33). Each involves a set of assumptions and a mixture of strengths and limitations; however, taken together, they have substantial power.…”
Section: Causal Effects Of Early Experiencesmentioning
confidence: 99%
See 1 more Smart Citation